Notch signaling genes and CD8+ T‐cell dynamics: Their contribution to immune‐checkpoint inhibitor therapy in oral squamous cell carcinoma: A retrospective study - Kazuhiro Ogi; Takahiro Iwamoto; Takashi Sasaya; Koyo Nishiyama; Takaaki Tokura; Takanori Sasaki; Hironari Dehari; Yohei Arihara; Kazuyuki Murase; Masato Saito; Masanori Someya; Kohichi Takada; et al. (Cancer Medicine, 2024)
Abstract Background Aberrant Notch signaling pathway has been related with the tumorigenesis in head and neck region, involving oral cavity. Here, we report the correlation between mutations in the Notch signaling pathway and CD8+ T‐cell infiltration via PD‐L1, which lead to enhanced antitumor immunity and may target for immune‐checkpoint inhibitors (ICIs) therapy. Methods This retrospective study analyzed the results of immunohistochemical staining for PD‐L1 and CD8+ T‐cell infiltration in 10 patients and whole‐exome sequencing (WES) was conducted on five of these patients to identify frequently mutated genes. Results Four of 10 patients were positive for PD‐L1 and CD8+ T. By analyzing WES in three of these four patients, we notably identified the mutations of NOTCH1, FBXW7, and noncoding RNA intronic mutation in NOTCH2NLR in two of these three patients. This study may enable better selection of ICI therapy with CD8+ T‐cell infiltration via PD‐L1 expression for oral squamous cell carcinoma patients with mutations in Notch signaling pathway.